Medicago sativa, a supplement in broiler chicken feed - Saavedra Sarmiento, Heráclides Hugo; Rojas Paredes, Marco Antonio; González Puetate, Iván (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
Agricultural sciences are responsible for the production of animal protein, where they must prioritize the continuous improvement of animal welfare, quality and quantity of meat per animal in production and usefulness in poultry systems, in search of alternatives to offer an adequate feeding in broilers. In the present research, 45 male broilers of the Cobb 500 line (43 g/ 1 day) were supplemented with chopped alfalfa (Medicago sativa), divided into treatment 0 (T0) or control without alfalfa supplementation, treatment 1 (T1) with 2,5% of alfalfa inclusion and 5% for treatment 2 (T2). It was observed that the increasing levels of chopped alfalfa (%) had a significant influence (p>0,05) on the variables evaluated, obtaining the best results with an inclusion level of 2,5% in each variable.
Keywords: Medicago sativa; Broilers; Poultry